Epitheloid granuloma of bone marrow- not always tuberculosis, think beyond what you see - Sneha, Latha M.; Thayammal, Indhuumathy S.; Priyathersini, Nagarajan; Vilvanathan, Vairan (International Journal of Contemporary Pediatrics, 2021)
Extra pulmonary tuberculosis has varied presentations and hence fever of unknown origin, with malaise, weight loss and cytopenias is generally attributed to tuberculosis in endemic regions. Tuberculosis being the most frequent cause of bone marrow granulomas, there is a risk of labelling granulomatous lesions as of infectious etiology when underlying etiology has an atypical presentation. Progressive painless lymphadenopathy, most commonly involving the cervical or supraclavicular area is the commonest presentation of Hodgkin’s lymphomas (HL) in 80%. Primary extra nodal presentation of HL is rare. We describe a case of an adolescent girl who presented with fever of unknown origin, weight loss, malaise, hematological derangements and bone marrow showing granuloma, all features pointing towards an infectious etiology, but later proven to be a case of HL.